Metal oxide based nanostructure engineering: electrical and gas sensitive properties of structurally modified SnO2 nanowires - Dmitriev, Serghei (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)

(untitled)
The paper presents results of the research aimed at the engineering of nanostructures